Counting Blessing: The Effect of Gratitude Training on Prosocialness among Teachers in Inclusive School - ika febrian kristiana; Erin Ratna Kustanti; Salma Salma (Universitas Ahmad Dahlan, 2021)
Gratitude can motivate everyone to be pro-socially behaved, create a positive social relation, and build the sense of togetherness in the school community. This research examines to measure the effect of gratitude training on teacher’s prosocial behavior in inclusive school with special need student (SEN). This is the quasi experimental research. There were 120 subjects divided into two groups, control and experiment. The treatment given to the experiment group was gratitude training. Data collected by using the sixteen items of the prosocialness scale for adults by Caprara et.al (2005) that has an excellent reliability (ω=0.980, 95%CI=0.972,0988) and distributed twice on pre and post-test. Statistical analysis showed (rB=0.339, p=.001, Hodges’ g=-3.000, 95% CI=-5.00, -1.00) that is means gratitude training have had an effect that tends to be moderate to the teacher’s prosocialness. However, this research’s findings display that gratitude is one of important psychological strength to motivate teachers’ prosocialness in inclusive school. This finding can serve as recommendations for prosocialness improvement programs for inclusive teachers in Indonesia with all its realities.